Klasifikasi Berbasis Algoritma C4.5 untuk Deteksi Kenaikan Case Fatality Rate Demam Berdarah - Andriani, Anik (Seminar Nasional Informatika Medis (SNIMed), 2017)
Extraordinary Events Dengue often occurs in Indonesia which causes patients died that affects the percentage deaths due to Dengue increased. It’s called Case Fatality Rate (CFR) Dengue. The government’s target on CFR Dengue is less than 1%. But CFR Dengue in some provinces in Indonesia is over 1%. Application of classification technique with C4.5 algorithm in this cases to know data pattern from CFR Dengue dataset in all province in Indonesia. Analysis process from historical data used for classification process applies stages of Knowledge Discovery in Databases consist of nine stages. The Classification result is Classification rule. It can describe data pattern extracted from CFR Dengue dataset. One of utilization to knowing the most influence factors to increase of CFR Dengue in a province. Classification result are evaluated by Confusion Matrix and ROC (Receiver Operating Characteristic) curve to know classification result performance’s. Evaluation result is known performance of classification rule generated into Excellent category.